Assessment of pulsed dielectrophoretic-field flow fractionation separation coupled with fibre-optic detection on a lab-on-chip as a technique to separate similar bacteria cells - Kamuri, Mohd Firdaus; Abidin, Zurina Zainal; Yaacob, Mohd Hanif; Hamidon, Mohd Nizar (Korean Society for Biotechnology and Bioengineering, 2024)
This study addresses the challenge of separating bacteria with similar structures such as Escherichia coli and Aeromonas hydrophila. This approach employs pulsed field dielectrophoresis assisted by laminar flow fractionation in a lab-on-a-chip system with integrated optical detection. Bacterial cells passed through 30-µm microelectrodes subjected at 1 MHz and 14 V peak-to-peak in pulsed mode, while fluid flow carried bacteria towards the chamber’s end. The on-and-off electric field at specific pulse intervals expose bacterial cells to diverse forces, including kinetics, dielectrophoresis, gravity, drag, and diffusion, resulting in a net force facilitating their movement. Variations of pulsing time, flow rates, and voltage were investigated to identify the optimal combination for efficient separation. Next, the bacteria were detected using an optical fibre based on their absorbance. Results demonstrated a 30 separation efficiency in 90 min at 9.6 μL min−1 flow rates, 4 s pulsing time, and 40 μS cm−1 medium conductivity. A. hydrophila aggregates experienced greater DEP force and retained at microelectrodes during electric field application compared to E. coli, which moved faster towards optical detection. The separation mechanism with and without electric field was different, and precise control of cell movement during field-off periods is important to minimize uncontrolled diffusion. While the optical detection part has been successful, longer time and separation length are recommended for better separation. A carefully tuned combination of pulsing time, flow rates, voltage, and microelectrode design is crucial for this integrated lab-on-chip system to be efficient for separating and detecting closely related microorganisms.